Safety and efficacy of daclizumab in relapsing-remitting multiple sclerosis: 3-year results from the SELECTED open-label extension study. Issue 1 (December 2016) - Gold, Ralf; Radue, Ernst-Wilhelm; Giovannoni, Gavin; Selmaj, Krzysztof; Havrdova, Eva; Stefoski, Dusan; Sprenger, Till; Montalban, Xavier; Cohan, Stanley; Umans, Kimberly; Greenberg, Steven; Ozen, Gulden; et al.
Abstract Background Daclizumab is a humanized monoclonal antibody against CD25 that modulates interleukin 2 signaling. The SELECT TRILOGY of clinical studies (SELECT/SELECTION/SELECTED) evaluated the safety and efficacy of daclizumab in patients with relapsing-remitting multiple sclerosis (RRMS). We report the long-term safety and efficacy of daclizumab 150 mg subcutaneous every 4 weeks in patients with RRMS in the SELECTED open-label extension study. Methods An interim intent-to-treat analysis of all enrolled patients was performed in January 2014 for this ongoing study. Results The SELECTED study enrolled 90 % of patients who completed SELECTION. In the safety and efficacy analysis (N  = 410), median treatment time in SELECTED was 25 months (range, <1–45). Adverse events (AEs) were reported in 76 % of patients, serious AEs (SAEs) excluding MS relapse in 16 %, and treatment discontinuation due to AEs including multiple sclerosis (MS) relapse in 12 %. AEs were primarily of mild to moderate severity, and common AEs (≥10 %), excluding MS relapse, were nasopharyngitis (12 %) and upper respiratory tract infection (12 %). Most commonly reported SAEs (in ≥3 patients), excluding MS relapses, were increased serum hepatic enzymes, pneumonia, ulcerative colitis, and urinary tract infection (<1 % each). Incidences of AE groups of interest include cutaneous events (28 %), cutaneous SAEs (2 %), gastrointestinal SAEs (2 %), hepatic SAEs, (1 %) and malignancies (1 %). The incidence of AEs, SAEs, and treatment-related study discontinuations did not increase over time and no deaths were reported. The adjusted annualized relapse rate (95 % confidence interval (CI)) analyzed at 6-month intervals was 0.15 (0.10–0.22) for weeks 97–120 and 0.15 (0.10–0.21) for weeks 121–144. In year 3, the adjusted mean (95 % CI) number of new/newly enlarging T2 hyperintense lesions was 1.26 (0.93–1.72) and the mean (median) annualized change in brain volume was −0.32 % (−0.34 %). Conclusions The AE incidence did not increase with extension of therapy into year 3 in SELECTED; the safety profile was similar to that previously observed. The clinical efficacy of daclizumab was sustained over the 3 years comprising the SELECT TRILOGY, although potential selection bias cannot be excluded. Trial registration Clinicaltrials.govNCT01051349 ; first registered January 15, 2010.